Dirofilariasis: An ignored parasitic zoonosis (International Seven Journal of Multidisciplinary, 2023)
Dirofilariasis is caused by Dirofilaria immitis, or dog heartworm, is a worldwide disease transmitted by mosquitoes of the genera Aedes, Anopheles, Culex and Taeniorhynchus; in humans, this filaria causes mainly cutaneous and pulmonary lesions, although cases have been reported with different locations such as large mesenteric vessels, peritoneal, spermatic cord and right side of the heart. In humans, unlike dogs, there is no filaremia. Symptoms in canines are inapparent and nonspecific, even asymptomatic. In humans, it is identified in chest X-rays as a coin-shaped lesion which tends to be confused with neoplastic lesions, infectious diseases or granulomas. In veterinary medicine in our country the mentioned cases of dirofilariasis were isolated, therefore it is important to highlight that in the last 10 months the presence of microfilaria nematodes was identified by blood cytology in 10 canines residing in Asuncion with non-specific clinical symptoms, which were submitted to specific treatment and favorable therapeutic response. It is important to reiterate the increase in the number of cases identified recently, which is relatively alarming due to the zoonotic viability of the disease. For this reason, the objective of this work is to communicate the exponential presence of cases of canine dirofilariasis to be included in the range of human differential diagnoses due to its zoonotic potential.